The Market and the State
XV, 259 p.
Keywords: The connection between markets and states is one of the great themes of political science. The contributors tackle the theme in uniquely varied ways: through the eyes of historians of ideas and analytical political philosophers: from the vantage points offered by the market-state balance in Latin America, Africa and Eastern Europe: and through analyses of how states regulate some of the most important sectors of advanced industrial economies.